A through-process, thermomechanical model for predicting welding-induced microstructure evolution and post-weld high-temperature fatigue response. (July 2018) - Mac Ardghail, P.; Harrison, N.; Leen, S.B.
Highlights: Process-structure-property welding simulation for 9Cr steels. Microstructure evolution predicted based on empirical models from test data. Physically-based constitutive model to predict temperature-dependent response. Post-weld heat treatment shown to increase predicted fatigue life. Abstract: This paper is concerned with the development of a modelling framework to predict the effects of welding and post-weld heat treatment on thermo-mechanical performance of welded material, as a step towards a design tool for industry. A dislocation mechanics, through-process finite element model, incorporating thermal, microstructural and mechanical effects is presented, for predicting thermo-mechanical fatigue of welds. The model is applied to multi-pass gas tungsten arc welding of 9Cr martensitic steel. The predicted high-temperature low-cycle fatigue performance of cross-weld samples is comparatively assessed for a range of different post-weld heat treatment durations. It is shown that longer post-weld heat-treatment (PWHT) durations increase the predicted number of cycles to failure and that Vickers hardness gradient across the heat-affected zone can be used as an indicator of fatigue life.